EFEKTIVITAS KEBERHASILAN SELF MANAGEMENT NYERI PADA PASIEN HERNIA NUKLEUS PULPOSUS (HNP): SYSTEMATIC REVIEW - Damianus Marissing,; Maria Astrid, (Journal of Innovation Research and Knowledge, 2025)
Introduction: Herniated Nucleus Pulposus is a tear in the annulus fibrosus of the intervertebral disc, and the nucleus pulposus comes out through the tear in the annulus fibrosus, resulting in compression of the spinal nerve roots. Clinical symptoms of HNP vary according to several factors such as the location (level) of herniation and nerve compression. HNP can cause pain, but the main clinical manifestations are radiating pain and sensitive changes that include the distribution of nerves. Several researchers have recommended methods to relieve pain in HNP through therapy to effective medical treatment